Winter feeding of the Crane in cereal farmland at Gallocanta, Spain - Alonso, Juan C; Alonso, Juan C; Veiga, Jos (Wildfowl, 1984)
The numbers, distribution and feeding habits of Cranes Grus grus were studied in relation to food availability in a cereal-growing farmland at Laguna de Gallocanta, Spain, from October 1981 to March 1983. The seasonal variation patterns of bird numbers and food availability are similar, both showing peaks in autumn and spring and a minimum in January. The correspondence is higher in zones adjacent to the roost, suggesting that birds prefer to forage as close to the roost as possible. Poor feeding conditions in mid-winter determine a decrease in the mean flock size and a higher dispersion of the birds, as well as a reduction in the wintering population size. Cranes utilize cultivated ground and natural grasslands as feeding areas. Sunflower stubble fields are strongly selected in autumn, while cereal stubble and sown fields are mainly utilized in autumn and spring respectively. Natural grasslands are positively selected.